Emotional Intelligence and Organizational Justice towards Counterproductive Work Behavior - Aulia Fajar Tiansari; Puti Archianti Widiasih (Universitas PGRI Yogyakarta, 2024)
Counterproductive work behavior is a common phenomenon that is a problem in human resources, employee behavior itself is a topic that is interested in research because behavior itself can influence the success of an organization in achieving predetermined goals This research aims to determine the Influence of emotional intelligence and organizational justice towards counterproductive work behavior. This is a quantitative research type. The research subjects involved account officer employees. The research data sources were from primary data and secondary data. Primary data was observed using a questionnaire (Google form), while secondary data was from employee data, books, and scientific journals. The research results reveal that a significant influence between emotional intelligence and organizational justice on counter-productive work behavior was found, seen from R square, namely 0.543 or 54.3% and the rest was influenced by other variables. Keywords: emotional intelligence, organizational justice, work behavior, counterproductive